Promoting Sustainable Development Through Environmental Policy, Green Technologies, and Effective Waste Management: A Comprehensive Review - Behera, Deepak Kumar (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Sustainable development is a global imperative achieved through environmentally conscious policies, green technology adoption, and efficient waste management. This comprehensive review examines the intertwined roles of environmental policy, green technologies, and waste management in advancing sustainability. It investigates the significance of policy and governance in setting environmental standards, emphasizes green technologies' transformative potential, explores renewable energy integration, delves into sustainable urban planning, and underscores effective waste management. Environmental policy and governance establish the framework for environmental protection, necessitating robust policies and penalties. Green technologies drive sustainability by curbing emissions and optimizing resource use across sectors. Integrating renewables demands smart grid innovation for stability. Sustainable urban planning fosters eco-friendly cities with energy-efficient buildings, public transit, and waste strategies. Waste management policies encourage reduction, recycling, and safe disposal. Aligning policy, green tech, and waste management is pivotal for sustainable development.